Answer:
x= 4 and y=3
Explanation:
-x+2y= 2 (Equation 1)
-x+y= -1 (Equation 2)
There are basically three methods of solving problems on simultaneous equation. Substitution method, Elimination method and graphical method.
Let's see how to use the substitution method.
Make y the subject of the formulae in equation 2:
-x+y= -1
y = -1+x
Substituting y for -1+x in equation 1, we have
-x + 2(-1+x) =2
-x -2+2x= 2
Let's collect like terms
-x+2x= 2+2
x = 4
Solving for y in equation 2, by substituting x with 4
-(4) +y= -1
y= -1+4
y=3
Using elimination method. First we subtract equation 2 from 1 to eliminate x
-x+2y=2
-x+y=-1
y=2+1=3
Substituting for y by 3 in equation 2.
-x+3=-1
3+1=x
x=4